The Use of Metaphor Function in The Song Lyrics in The Album “Time Machine” By Pusakata - Nasruddin, Anis; Setiana, Leli Nisfi; Wardani, Oktarina Puspita (Universitas Negeri Semarang, 2025)
Difficulty understanding changes in meaning in the use of metaphorical language styles is often experienced, especially by lay people. This research aims to analyze the metaphors in the song lyrics on the album Machine Time by Pusakata using qualitative descriptive methods. The research process involves the steps of recording, grouping and understanding metaphors based on type and function, as well as their relevance to learning to write poetry in class X. Data was collected through text analysis and documentation. The lyrics of the song Pusakata in the album Machine Time are rich in metaphors which not only enrich the text, but also have great potential to be utilized in literature learning. The metaphors in the lyrics help create poetic images that deepen meaning and increase appreciation of the language. In the context of learning to write poetry, this exploration of language styles allows students to be more creative and expressive in their written work. In accordance with the problem formulation, researchers conducted research with the following objectives. a). Describe the types of metaphors in the heritage songs on the album